Pembentukan Perilaku Digital Mad’u melalui Pendekatan Psikologi Dakwah: Studi tentang Internalisasi Nilai dalam Lingkungan Media Sosial - Ahmad Tarmizi susanto; Tahrudin; Mu"taeri; Meity Suryandari (Journal of Education and Learning Sciences, 2026)
The rapid development of digital technology has significantly transformed patterns of social interaction, particularly through the widespread use of social media, which plays a crucial role in shaping the behavior of mad’u in the digital environment. This study aims to examine how digital behavior is formed through the internalization of values within social media using a da’wah psychology approach. The research addresses the question of how value internalization occurs and how it influences the behavior of mad’u in the digital era. This study employs a library research approach by analyzing relevant scholarly literature, including recent journal articles and academic sources. The findings indicate that digital behavior formation is influenced by several factors, including the intensity of social media use, content exposure, social reinforcement, and the dynamics of digital environments. The internalization of values often occurs superficially due to information overload and the dominance of entertainment-oriented content. From the perspective of da’wah psychology, effective value internalization requires the integration of cognitive, emotional, and spiritual dimensions. The study concludes that a da’wah psychology approach is essential in shaping ethical and value-based digital behavior. The integration of adaptive, contextual, and psychologically grounded da’wah strategies can enhance the effectiveness of value internalization, thereby fostering digitally responsible and spiritually grounded mad’u in the era of social media.